Obedience in perspective: Psychology and the Holocaust. (October 2015) - Mastroianni, George R.
Stanley Milgram's explanation of the Holocaust in terms of the mechanism of obedience is too narrow. While obedience was one mechanism which contributed to the outcome, the murder of Jews and others was the work of people from a broad swath of German society, from economists who planned mass starvation to ordinary soldiers in the Wehrmacht, often acting without duress or apparent pressures to conform. Psychologists should not ask "why?" the Holocaust occurred, but "how?" Much behavior of perpetrators, bystanders, victims, and instigators can be understood as the consequence of normal mechanisms of perception, learning, socialization, and development. What made genocide possible was not the transitory conditions created in a lab in a few hours but a complex of mechanisms that are the product of generations of human experience and of elaborate rational, emotional, and logical justifications. This requires a more complex future psychology than the narrow focus on situationist obedience.